Exploiting coherence for real‐time studies by single‐bunch imaging. (9th May 2014) - Rack, A.; Scheel, M.; Hardy, L.; Curfs, C.; Bonnin, A.; Reichert, H.
<x xml:space="preserve">Abstract</x> First real‐time studies of ultra‐fast processes by single‐bunch imaging at the European Synchrotron Radiation Facility are reported. By operating the storage ring of the ESRF in single‐bunch mode with its correspondingly increased electron bunch charge density per singlet, the polychromatic photon flux density at insertion‐device beamlines is sufficient to capture hard X‐ray images exploiting the light from a single bunch (the corresponding bunch length is 140 ps FWHM). Hard X‐ray imaging with absorption contrast as well as phase contrast in combination with large propagation distances is demonstrated using spatial samplings of 11 µm and 35 µm pixel size. The images acquired allow one to track crack propagation in a bursting piece of glass, breaking of an electrical fuse as well as cell wall rupture in an aqueous foam. Future developments and their potential in the frame of the proposed Phase II of the ESRF Upgrade Program are discussed.